Times of crisis, times of imbalance, times precarious, times of woman - Larrañaga, Mertxe; Jubeto, Yolanda; de la Cal, Mª Luz (Investigaciones Feministas (Feminist Research), 2012)
The main aim of this article is to analyse how the current global crisis is impacting on women and men in Spain, within the European context. In that sense, it covers the analysis of the effects that the crisis and the policies currently carried out seemingly to overcome it, are having on the lives and works of women and men, taking into account the available statistics. The study will involve the effects of this crisis on the productive sphere as well as on the reproductive one. The article finishes with a battery of basic proposals intended to face this situation from a feminist perspective.